Feasibility of an MI-CBT ketogenic adherence program for older adults with mild cognitive impairment - Julia L. Sheffler; Bahram Arjmandi; Jamie Quinn; Greg Hajcak; Cynthia Vied; Neda Akhavan; Sylvie Naar (Pilot and Feasibility Studies, 2022)
Abstract Background The National Institutes of Health Obesity-Related Behavioral Intervention Trials model for intervention development was used to establish the feasibility and proof of concept of a motivational ketogenic nutrition adherence program for older adults with mild cognitive impairment. Methods This was a single-arm, single-center feasibility trial. A comprehensive assessment protocol, including a clinical interview, neuropsychological testing, and genetic sequencing was used as an initial screening. Nine participants (aged 64–75) with possible amnestic mild cognitive impairment were consented for the intervention. Participants completed pre- and post-intervention neuropsychological assessments using the updated Repeatable Battery for Assessment of Neuropsychological Status. Participants tracked their macronutrient consumption using food diaries and ketone levels using urinalysis test strips daily. Mood and other psychosocial variables were collected through surveys, and qualitative exit interviews were completed. Results 100% of participants who began the trial completed the 6-week ketogenic nutrition adherence program, including completion of the pre- and post-assessments. Eight participants achieved measurable levels of ketones during the program. The average self-rated adherence across the program was 8.7 out of 10. A Wilcoxon Signed-Rank test demonstrated significant improvement in cognitive performance from baseline (median = 88) to follow up (median = 96, Z = − 2.26, p = .024). The average difference in cognitive performance from baseline to follow-up was − 7.33 (95% CI − 12.85, − 1.82). Conclusions Results supported the feasibility for moving to the next phase and demonstrated proof of concept for the intervention. The next step is a randomized pilot trial to test clinical signals of effect compared to a control condition. Trial registration This trial was retrospectively registered with clinicaltrials.gov on July 13, 2021. The trial number is NCT04968041.